1998
DOI: 10.1038/36103
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent scaling of quantal amplitude in neocortical neurons

Abstract: Information is stored in neural circuits through long-lasting changes in synaptic strengths. Most studies of information storage have focused on mechanisms such as long-term potentiation and depression (LTP and LTD), in which synaptic strengths change in a synapse-specific manner. In contrast, little attention has been paid to mechanisms that regulate the total synaptic strength of a neuron. Here we describe a new form of synaptic plasticity that increases or decreases the strength of all of a neuron's synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

139
2,214
14
8

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,040 publications
(2,375 citation statements)
references
References 28 publications
139
2,214
14
8
Order By: Relevance
“…This finding suggests a form of homeostasis that does not feature the regulation of average activity, that is, average firing rate of neurons (e.g. Turrigiano and Nelson, 2004), but instead suggests a homeostatic regulation of the diversity in spontaneous neuronal synchronization in the form of neuronal avalanches.…”
Section: Self-organized Criticality As a Homeostatic Principle Duringmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding suggests a form of homeostasis that does not feature the regulation of average activity, that is, average firing rate of neurons (e.g. Turrigiano and Nelson, 2004), but instead suggests a homeostatic regulation of the diversity in spontaneous neuronal synchronization in the form of neuronal avalanches.…”
Section: Self-organized Criticality As a Homeostatic Principle Duringmentioning
confidence: 97%
“…Accordingly, an nLFP cluster would represent a cascade of topplings on the grid. Although the exact nature of the driving that results in spontaneous cascade generation in the absence of inputs is currently not known, it is well established that neurons possess numerous intrinsic mechanisms that increase their likelihood to fire action potentials after prolonged periods of subthreshold activity (Turrigiano, Leslie et al, 1998;Thiagarajan, Lindskog et al, 2007). For organotypic cortex cultures, suppression of activity has been demonstrated to trigger numerous physiological responses that upregulate network activity (Corner, Baker et al, 2005).…”
Section: Self-organized Criticality As a Homeostatic Principle Duringmentioning
confidence: 99%
“…Neural systems have several different mechanisms (Bi and Poo 1998;Turrigiano et al 1998;Royer and Paré 2003;Zhou et al 2003), which are also used in theoretical studies (Rochester et al 1956;Bienenstock et al 1982;Riedel and Schild 1992;Van Rossum et al 2000) to avoid these runaway dynamics.…”
Section: Long-term Plasticitymentioning
confidence: 99%
“…A synaptic plasticity mechanism that seems to work on a longer time scale than minutes to hours is synaptic scaling (Turrigiano et al 1998;Turrigiano and Nelson 2004;Rabinowitch and Segev 2006;Tetzlaff et al 2011). Here, the synaptic efficiency of all inputs to a neuron increases/ decreases if the activity of this neuron is lower/higher than a target activity (Davis 2006).…”
Section: Long-term Plasticitymentioning
confidence: 99%
“…Turrigiano et al (1998) first demonstrated this form of homeostatic plasticity at excitatory synapses by showing that their strength was increased by the deprivation of neuronal activity and reduced by the enhancement of neuronal activity, as measured by fluctuations in the amplitude of miniature excitatory postsynaptic currents (mEPSCs). This activity-dependent scaling of excitatory synaptic strength has since been shown to be dependent on postsynaptic depolarization (Leslie et al, 2001) and brain-derived neurotrophic factor (BDNF) , a protein whose expression is induced by neuronal activity (Isackson et al, 1991;Lindholm et al, 1994;Berninger et al, 1995) and that has been implicated in multiple forms of synaptic plasticity (for a review, Poo, 2001).…”
Section: Introductionmentioning
confidence: 99%